2014
DOI: 10.1038/nature13319
|View full text |Cite
|
Sign up to set email alerts
|

Mass-spectrometry-based draft of the human proteome

Abstract: Proteomes are characterized by large protein-abundance differences, cell-type- and time-dependent expression patterns and post-translational modifications, all of which carry biological information that is not accessible by genomics or transcriptomics. Here we present a mass-spectrometry-based draft of the human proteome and a public, high-performance, in-memory database for real-time analysis of terabytes of big data, called ProteomicsDB. The information assembled from human tissues, cell lines and body fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

61
1,691
8
11

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,704 publications
(1,825 citation statements)
references
References 46 publications
61
1,691
8
11
Order By: Relevance
“…Comprehensive studies on the proteomes of cells, tissues, or organisms have been reported (e.g. Addona et al , 2009; Nilsson et al , 2010; Beck et al , 2011; Nagaraj et al , 2011; for review, see Bensimon et al , 2012; Kulak et al , 2014; Wilhelm et al , 2014; Hein et al , 2015; Richards et al , 2015), but accurate quantitative information on proteins expressed at low levels remains scarce. As a consequence, published estimates for the abundance of specific proteins sometimes vary over several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive studies on the proteomes of cells, tissues, or organisms have been reported (e.g. Addona et al , 2009; Nilsson et al , 2010; Beck et al , 2011; Nagaraj et al , 2011; for review, see Bensimon et al , 2012; Kulak et al , 2014; Wilhelm et al , 2014; Hein et al , 2015; Richards et al , 2015), but accurate quantitative information on proteins expressed at low levels remains scarce. As a consequence, published estimates for the abundance of specific proteins sometimes vary over several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Several such generic repositories are now available, for example PRIDE 4, GPMDB 5, PeptideAtlas 6, and MassIVE (http://massive.ucsd.edu/ProteoSAFe) for shotgun results; and PASSEL 7, SRMAtlas (http://www.srmatlas.org), and Panorama 8 for targeted proteomics quantification data. More specific databases have also been established, related to: diseases, for example TBDB for tuberculosis 9; organisms, for example ProteomicsDB 10 and the Human Proteome Map 11 for the human proteome, and pep2pro for Arabidopsis 12; or subproteomes, for example CSF‐PR 13 for cerebrospinal fluid or TOPPR 14 and TopFIND 15 for in vivo cleaved proteins. For a comprehensive overview of the current proteomics databases and repositories, please see Perez‐Riverol et al 16.…”
Section: Introductionmentioning
confidence: 99%
“…Note that it is also possible to develop tools to look for novel transitions in publicly available shotgun datasets. For example, MRMaid 34, PeptidePicker 35, 36, and ProteomicsDB 10 do this by reusing identification data coming from PRIDE and other sources.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations